Simple sequences are ubiquitous repetitive components of eukaryotic genomes. - Tautz, D (1984)
Simple sequences are stretches of DNA which consist of only one, or a few tandemly repeated nucleotides, for example poly (dA) X poly (dT) or poly (dG-dT) X poly (dC-dA). These two types of simple sequence have been shown to be repetitive and interspersed in many eukaryotic genomes. Several other types have been found by sequencing eukaryotic DNA. In this report we have undertaken a systematical survey for simple sequences. We hybridized synthetical simple sequence DNA to genome blots of phylogenetically different organisms. We found that many, probably even all possible types of simple sequence are repetitive components of eukaryotic genomes. We propose therefore that they arise by common mechanisms namely slippage replication and unequal crossover and that they might have no general function with regards to gene expression. This latter inference is supported by the fact that we have detected simple sequences only in the metabolically inactive micronucleus of the protozoan Stylonychia, but not in the metabolically active macronucleus which is derived from the micronucleus by chromosome diminution.